Contact analysis and mathematical modeling of traveling wave ultrasonic motors - Zhu, Meiling (Institute of Electrical and Electronics Engineers (IEEE), 2004)
An analysis of the contact layer and a mathematical modeling of traveling wave ultrasonic motors (TWUM) are presented for the guidance of the design of contact layer and the analyses of the influence of the compressive force and contact layer on motor performance. The proposed model starts from a model previously studied but differs from that model in that it adds the analysis of the contact layer and derives the steady-state solutions of the nonlinear equations in the frequency domain, rather than in the time domain, for the analyses of vibrational responses of the stator and operational characteristics of the motor. The maximum permissible compressive force of the motor, the influences of the contact layer material, the thickness of the contact layer, and the compressive force on motor performance have been discussed. The results show that by using the model, one can understand the influence of the compressive force and contact layer material on motor performance, guide the choice of proper contact layer material, and calculate the maximum permissible compressive force and starting voltage.
Keywords: Traveling wave ultrasonic motors; contact analysis